The Conley index over a phase space for flows - Szybowski, Jacek (Topological Methods in Nonlinear Analysis, 2012)
We construct the Conley index over a phase space for flows. Ourdefinition is an alternative for the Conley index over a basedefined in [M. Mrozek, J.F. Reineck and R. Srzednicki, < i> The Conley index over a base< /i> , Trans. Amer. Math. Soc. < b> 352< /b> (2000), 4171-4194]. We also compare it to other Conley-typeindices and prove its continuation property.